Role of Q-Commerce Instant Gratification on Customer Satisfaction : The Moderating Effect of Green Packaging - Chavadi, Chandan A.; Kokatnur, Shilpa S.; Sirothiya, Monika (Indian Journal of Marketing, 2024)
Purpose : This research investigated the role of Q-commerce instant gratification on customer satisfaction, employing the stimulus-organism-behavior-consequence framework. Methodology : We collected 428 survey responses from Indian consumers who had used the Q-commerce apps through purposive and stratified sampling. Subsequently, we employed structural equation modeling to analyze the data collected. Findings : The results revealed that instant gratification had a positive influence on customer engagement, experience, and satisfaction. Additionally, customer satisfaction affected repurchase intention and word-of-mouth (WOM), and green packaging significantly moderated the association between customer satisfaction, WOM, and repurchase intention. Practical Implications : The research outcomes may hold importance for Q-Commerce companies looking to enhance customer satisfaction through quick deliveries and sustainable packaging practices. Originality : The research contributed by using the stimulus-organism-behavior consequences framework in an emerging field, contributing to the body of scholarly literature.